Strategi Pemasaran Untuk UMKM Melalui Pemanfaatan Media Sosial dan Teknologi Informasi - Mugiarso; Setiawan, Septhiyanthi; Hilmy Dwinanda, Muhammad; Arby Ansya, dkk, Muhammad (VINICHO MEDIA PUBLISINDO, 2023)
Before the era of Information Technology, Micro, Small and Medium Enterprises (MSMEs) were faced with a number of problems that could hinder their development. Limited market access and lack of information about market trends and customer preferences often make it difficult for MSMEs to develop effective marketing strategies. Observation activities are carried out by conducting direct observations of the situation and environmental conditions of the community. MSMEs now have the opportunity to overcome most of these problems. The aim of MSMEs in Sawarna Village is to carry out marketing that can improve the quality of human resources who have high abilities and interest in marketing the Sitaman Bumi application, Batour. Utilization of online platforms that will be used to help MSMEs